Crusade and Its Effect on the East and the West - Ahmad Sahide (Graduate Program of Pontianak Institute of Islamic Studies, 2015)
The Crusade is an important part of the history of Islamic thought, development, culture and civilization. The Crusade which changed the path of human historical development, especially of the Islamic world, had a major influence on the encounter between the West and the East (the Islamic world) today. By understanding the history, the Crusade, we can find the correlation of the hegemony of the Western countries, especially between the United States and the Islamic world today, especially in the Middle the East region. the Western presence in all aspects of life of the contemporary Islamic world, which is far left behind, has historical relevance of the Crusade. This paper seeks to review the Crusade and its influence on the development of the contemporary Islamic world and the West.